Lingkar Pinggang, Kekuatan Genggam, dan Diet DASH: Faktor yang Berhubungan dengan Tekanan Darah Pasien Hipertensi di Rumah Riset Jamu Hortus Medicus - Novita Fitri Anggraeni; Adhila Fayasari (Journal Malnutrition, Public Health and Local Wisdom Nutrition, 2026)
Hypertension is a public health problem associated with central obesity, muscle strength, and dietary patterns. This study aimed to analyse the associations of waist circumference, handgrip strength, and adherence to the Dietary Approaches to Stop Hypertension (DASH) diet with blood pressure among pre-elderly and elderly hypertensive patients at the Hortus Medicus Jamu Research Centre, Tawangmangu. This cross-sectional study used secondary data from a parent study conducted in August–September 2024. Of 100 patient records, 85 met the inclusion criteria and were analysed. Waist circumference was measured using an anthropometric tape, handgrip strength using a handgrip dynamometer on the dominant hand, blood pressure using a digital sphygmomanometer, and dietary adherence using a DASH score. Univariate and bivariate analyses used the Chi-square test or Fisher’s exact test, stratified by sex, at a 95% confidence level. Most respondents had central obesity (70.6%), suboptimal systolic blood pressure (89.4%), and low DASH diet adherence (51.8%). None of the three variables was significantly associated with systolic blood pressure (p > 0.05). A significant association was found only between handgrip strength and diastolic blood pressure among women (p = 0.034). Handgrip strength may serve as a cardiometabolic risk indicator among pre-elderly and elderly women. Keywords: blood pressure; DASH diet, elderly, handgrip strength, waist circumference